Nano-Drug Delivery Systems in Oral Cancer Therapy: Recent Developments and Prospective - Yun Zhang; Yongjia Wu; Hongjiang Du; Zhiyong Li; Xiaofeng Bai; Yange Wu; Huimin Li; Mengqi Zhou; Yifeng Cao; Xuepeng Chen (MDPI AG, 2023)
Oral cancer (OC), characterized by malignant tumors in the mouth, is one of the most prevalent malignancies worldwide. Chemotherapy is a commonly used treatment for OC; however, it often leads to severe side effects on human bodies. In recent years, nanotechnology has emerged as a promising solution for managing OC using nanomaterials and nanoparticles (NPs). Nano-drug delivery systems (nano-DDSs) that employ various NPs as nanocarriers have been extensively developed to enhance current OC therapies by achieving controlled drug release and targeted drug delivery. Through searching and analyzing relevant research literature, it was found that certain nano-DDSs can improve the therapeutic effect of drugs by enhancing drug accumulation in tumor tissues. Furthermore, they can achieve targeted delivery and controlled release of drugs through adjustments in particle size, surface functionalization, and drug encapsulation technology of nano-DDSs. The application of nano-DDSs provides a new tool and strategy for OC therapy, offering personalized treatment options for OC patients by enhancing drug delivery, reducing toxic side effects, and improving therapeutic outcomes. However, the use of nano-DDSs in OC therapy still faces challenges such as toxicity, precise targeting, biodegradability, and satisfying drug-release kinetics. Overall, this review evaluates the potential and limitations of different nano-DDSs in OC therapy, focusing on their components, mechanisms of action, and laboratory therapeutic effects, aiming to provide insights into understanding, designing, and developing more effective and safer nano-DDSs. Future studies should focus on addressing these issues to further advance the application and development of nano-DDSs in OC therapy.